Trillin on Texas - Trillin, Calvin (University of Texas Press, 2021)
"Yes, I do have a Texas connection, but, as we say in the Midwest, where I grew up, not so's you'd know it." So Calvin Trillin introduces this collection of articles and poems about a place that turns up surprisingly often when he's ostensibly writing about something else. Whether reporting on the American scene for the New Yorker, penning comic verse and political commentary for the Nation, or writing his memoirs, Trillin has bumped into Texas again and again. He insists that "this has not been by design . . . there has simply been a lot going on in Texas." Astute readers will note, however, that Trillin's family immigrated to the United States through the port of Galveston, and, after reading this book, many will believe that the Lone Star State has somehow imprinted itself in the family's imagination. Trillin on Texas gathers some of Trillin's best writing on subjects near to his heart-politics, true crime, food, and rare books, among them-which also have a Texas connection.